People's Republic of China : Detailed Assessment Report: IAIS Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2012)
This paper presents a detailed assessment report on the observance of China's compliance with the International Association of Insurance Supervisor's insurance core principles. The China Insurance Regulatory Commission employs a rules-based framework and has achieved a high level of regulatory compliance from supervised companies. The market demand for skilled resources continues to increase and must be satisfied if the projected rate of development is to be sustained; compromises on the suitability of personnel should be avoided at all costs.